British travellers’ image perspectives of Brazil as a tourism destination - O’neil, Isobel (REVISTA ACADÊMICA OBSERVATÓRIO DE INOVAÇÃO DO TURISMO, 2008)
Over the last couple of years in Britain there has been an explosion of Brazilian favours in popular culture and the increased cultural interest in Brazil seems to be mirrored by an increased interest in Brazil by the travel and tourism sector. Therefore, mainstream operators are also looking to Brazil. However, it is also the case that Brazil has a reputation for insecurity due to gun crime and high crime levels relating to muggings against tourists. Otherwise, many positive organic image sources have raised the profile of Brazil in Britain. It is with this in mind that the following research under-took an exploratory study of British Travellers’ image perspectives as a tourism destination. Based on literature about destination image management and quantitative research, this study concludes that Brazil has a strong image, both before and after experience, regarding beautiful natural attrac-tions, beaches, the atmosphere, culture and people. Presently, the image of Brazil as a country for adventure sports and historical cities is weaker than that of sun and sea. British tourists after visita-tion have a less negative impression about issues related to crime and social problems.